Pengaruh Ekstra Buah Pala pada Mutu Ikan LayangAsap - Azis Husen (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Preservation is defined as an effort to maintain the quality of fish or extend the shelf life of fish so that the fish can still be used and consumed ingood and proper condition. The processing of smoked fish caused this condition by immersing nutmeg extract, which is only known in certain areas with limited consumers, such as in the city of Ternate, North Maluku. The purpose of this study was to determine the effect of nutmeg extract treatment and soaking time on the taste of smoked flying fish. This research consisted of two stages, namely the preparation of raw materials and the manufacture of smoked flying fish. By using organoleptic tests, namely appearance, smell, taste,and texture. The single factor utterly randomized design analysis. The results of immersion research concentrations of nutmeg extract were 0%, 10%, 15% and 20%. For the organoleptic value of appearance with an average value of 25.8, smell with an average value of 27.4, taste 31.2 and texture 31.4. Very influential on the quality characteristics of smoked flying fish for appearance, smell, taste, and texture of the product smoked flying fish, and organoleptic test results of smoked flying fish that have the best value are Texture 31.4 at 20% treatment, due to the high concentration of nutmeg extract, the panelists gave a high rating, which is very preferred.